BUILT ENVIRONMENT IMPACT TO MICROCLIMATE (AIR TEMPERATURE) - Syaiful Muazir; Lestari . (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2019)
In step with economic growth, Pontianak City continues developing its physical development. From an environmental perspective, physical development that does not pay attention to the environment may make air temperature rise and create inconvenience to human. The purpose of this study is to evaluate the tendency in the built/physical environmental aspects that have the possibility of influencing the microclimate in the urban center, regarding the trade area in Pontianak City. Built environmental aspects such as building density, building height, materials, etc. are described and then simulated towards the existing climate elements such as temperature, humidity, solar radiation, cloud cover, and others. The simulations used three-dimensional software ENVI_MET version 4. From findings, it can be seen that the built environment characteristics can affect the microclimate condition. From the simulations, the dominant temperature differences may occur in such built environment conditions such as density, dimensions, location, material, and vegetation closure.